Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3109/10715762.2010.535529
|View full text |Cite
|
Sign up to set email alerts
|

An assay for RNA oxidation induced abasic sites using the Aldehyde Reactive Probe

Abstract: There have been several reports describing elevation of oxidized RNA in aging or age-related diseases, however RNA oxidation has been assessed solely based on 8-hydroxy-guanosine levels. In this study, Aldehyde Reactive Probe (ARP), which was originally developed to detect DNA abasic sites was used to assess RNA oxidation. We found that ARP reacted with depurinated tRNA Phe or chemically synthesized RNA containing abasic sites quantitatively to as little as 10 fmoles, indicating that abasic RNA is recognized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…It was proposed that since RNA molecules are very similar to DNA, the oxidative lesions observed in DNA could also be observed on the corresponding bases in RNA [83], and these lesions may serve as marker of oxidative damage in RNA with increased accuracy. In the past years, the oxidized product of guanosine, 7,8-dihydro-8-oxo-guanosine (8-OHG), has been actively investigated [84]. 8-OHG is the most examined oxidation products of the RNA due to its similarity to the 8-oxoG lesion in DNA and the ability to use many of the same methodologies verified on DNA substrates for the analysis of RNA oxidation products.…”
Section: 8-dihydro-8-oxo-guanosine (8-ohg)mentioning
confidence: 99%
“…It was proposed that since RNA molecules are very similar to DNA, the oxidative lesions observed in DNA could also be observed on the corresponding bases in RNA [83], and these lesions may serve as marker of oxidative damage in RNA with increased accuracy. In the past years, the oxidized product of guanosine, 7,8-dihydro-8-oxo-guanosine (8-OHG), has been actively investigated [84]. 8-OHG is the most examined oxidation products of the RNA due to its similarity to the 8-oxoG lesion in DNA and the ability to use many of the same methodologies verified on DNA substrates for the analysis of RNA oxidation products.…”
Section: 8-dihydro-8-oxo-guanosine (8-ohg)mentioning
confidence: 99%
“…In bacteria, these target macromolecules include elongation factors Tu [30][31][32][33][34], Ts (EF-Ts) [32] and G (EF-G) [8,9,22,32,35], several ribosomal proteins [31,36,37], tRNA [38][39][40][41][42] and aminoacyl-tRNA synthetases (aaRS) [31,34,36,37,43,44] (Table 1). rRNA and mRNA has also been shown to be oxidized in vivo in eukaryotes [19,25,26], but in bacteria this has not been tested.…”
Section: Oxidation Of the Translation Machinery During Oxidative Stressmentioning
confidence: 99%
“…In this context, oxidation of RNA has been found in eukaryotes during oxidative stress, senescence or some age related diseases [19,25,26]. This reaction would depend on the ability of RNA to bind Fe +2 which catalyzes its oxidation.…”
Section: Oxidation Of Trnamentioning
confidence: 99%
See 1 more Smart Citation
“…The probe was found to penetrate the plasma membrane and react with the AP sites in DNA, which was then quantified by colorimetry after labeling with avidin-HRP [17]. Tanaka et al found that ARP could also be used to quantify the AP sites in RNA with a detection limit of 10 fmol [18]. Kojima et al improved the reaction rate of the probe by incorporating a hydrophobic and a hydrophilic residue into an aminooxy group [19].…”
Section: Introductionmentioning
confidence: 99%